Penguatan MGMP dalam membuat soal fisika Higher Order Thinking Skills (HOTS) - Kaharuddin Arafah; Muhammad Arsyad; Helmi Helmi (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The purpose of this activity was to providereinforcement to the Makassar City Physics Subject Teachers(MGMP) in formulating a question-making grid, constructingitems, analyzing items, calculating the validity and reliabilityof assessment instruments physics learning outcomes tomeasure Higher Order Thinking skills (HOTS). To achievethis goal, a workshop was held for Physics teachers who weremembers of the Makassar City Physics MGMP at SMAN 10Makassar as their secretariat. This workshop was held for 4weeks, every Saturday. In the first week reinforcement wasmade in the form of presentations on techniques for makinggrids, techniques for formulating items then continued with theassignment of making a grid for participants. Then in thesecond week, there was a discussion about the grid that hadbeen done by the participants, then continued with formulatingthe points which continued with the presentation of each group.All participants were asked to comment on items made byother participants. In the third week, presentations were madeby the dedicated team regarding item analysis techniqueswhich continued with the assignment of assignments toparticipants. Last week, there was a discussion about the itemsthat the participants had made to ensure that all the itemsproduced by the participants were included in the HOTScategory. The results showed that above 85% of the MGMPPhysics participants were able to produce Physics items thatwere included in the HOTS category.